Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan dengan Disiplin Kerja Sebagai Mediasi pada Karyawan PT. Bank Tabungan Negara Cabang Syariah Pekanbaru - Zulva Febriyanti; Desvi Emti (Al-Manar Journal of Accountancy and Business Studies, 2025)
This research was conducted at PT Bank Tabungan Negara Syariah Branch in Pekanbaru. The study aims to analyze the influence of leadership style and work motivation on employee performance, with work discipline acting as a mediating variable among employees of PT Bank Tabungan Negara Syariah Branch Pekanbaru. The research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to employees and analyzed using the Structural Equation Modeling (SEM) method via the SmartPLS application. The population in this study consisted of 62 individuals, all of whom were included as the sample. The results indicate that leadership style and work motivation do not have a direct effect on employee performance. However, both leadership style and work motivation have a direct influence on work discipline. Moreover, work discipline has been shown to mediate the relationship between leadership style, work motivation, and employee performance. The implications of this study suggest that companies need to pay close attention to developing positive leadership styles and motivational strategies that effectively encourage employees to enhance their performance.